Hubungan Pengetahuan Ayah tentang Bounding Attachment dengan Ikatan Tali Kasih Ayah dan Janin - Helda Fitriani Fidra; Misrawati; Widia Lestari (Universitas Bengkulu, 2023)
Emotional bond made with the fetus can affect the father’s psychology and keep the harmony in the relationship between the husband and the wife. Forming a bond between a father and a fetus needs knowledge on bounding attachment. This research aims at finding out the relationship between the father’s knowledge on bounding attachment and the father’s and the fetus’ love bond. This research uses correlation design with cross sectional approach. It uses 98 respondents as samples. Data analysis used are univariate and bivariate analyses with chi square test. This research shows a significant result that the father’s knowledge on bonding attachment is related to the father’s love bond towards the fetus (p = 0.000. OR = 0.4). It can be concluded that the father’s knowledge on bounding attachment is related to the father’s and the fetus’ love bond. This research can add to the learning and materials on bounding attachment that a father can do to the fetus in the beginning of the mother’s pregnancy. It will also be insightful for nursing students in the subject of maternity.